2017
DOI: 10.1038/s41598-017-00326-1
|View full text |Cite
|
Sign up to set email alerts
|

Egg antigen p40 of Schistosoma japonicum promotes senescence in activated hepatic stellate cells via SKP2/P27 signaling pathway

Abstract: Schistosomiasis is characterized by egg deposition, granulomatous inflammatory reaction and then subsequent hepatic fibrosis formation. Activated HSCs are regarded as the main effector cells in the progression of liver fibrosis and induction of senescence in hepatic stellate cells (HSCs) is vital to the reversion of hepatic fibrosis. Our previous work has showed that S. japonicum egg antigen p40 (Sjp40) could promote HSCs senescence via a STAT3/p53/p21 mechanism. In this paper, the major aim was to explore whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Schistosomiasis is a chronic parasitic disease affecting more than 250 million people in tropical and subtropical countries [1, 2]. Eggs of the three main Schistosoma species ( Schistosoma mansoni , S. haematobium and S. japonicum ) have been demonstrated to play a major role in human disease attributable to schistosomiasis, being involved in its morbidity, pathology, host immune modulation, diagnosis and transmission [3, 4]. A single female S. japonicum lays approximately 1000 eggs per day inside the veins of its mammal host [5].…”
Section: Introductionmentioning
confidence: 99%
“…Schistosomiasis is a chronic parasitic disease affecting more than 250 million people in tropical and subtropical countries [1, 2]. Eggs of the three main Schistosoma species ( Schistosoma mansoni , S. haematobium and S. japonicum ) have been demonstrated to play a major role in human disease attributable to schistosomiasis, being involved in its morbidity, pathology, host immune modulation, diagnosis and transmission [3, 4]. A single female S. japonicum lays approximately 1000 eggs per day inside the veins of its mammal host [5].…”
Section: Introductionmentioning
confidence: 99%
“…Schistosomiasis japonica is a chronic helminth infection of humans caused by S. japonicum [ 1 , 2 ]. The eggs of S. japonicum are deposited in the liver, lung, and intestinal wall and induce granulomatous inflammation and progressive fibrosis, which are the primary clinical pathological changes.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we found a combined effect of MYOD1 and STAT3 on accelerating fibronectin and collagen I production. Indeed, the involvement of STAT3 in ECM production was confirmed in renal and liver fibrosis . Therefore, more studies are needed to clarify regulatory mechanisms between MYOD1 and STAT3 in HTMCs.…”
Section: Discussionmentioning
confidence: 99%